Folic acid deficiency induces premature hearing loss through mechanisms involving cochlear oxidative stress and impairment of homocysteine metabolism. Issue 2 (10th November 2014) - Martínez‐Vega, Raquel; Garrido, Francisco; Partearroyo, Teresa; Cediel, Rafael; Zeisel, Steven H.; Martinez‐Alvarez, Concepción; Varela‐Moreiras, Gregorio; Varela‐Nieto, Isabel; Pajares, María A.
ABSTRACT: Nutritional imbalance is emerging as a causative factor of hearing loss. Epidemiologic studies have linked hearing loss to elevated plasma total homocysteine (tHcy) and folate deficiency, and have shown that folate supplementation lowers tHcy levels potentially ameliorating age‐related hearing loss. The purpose of this study was to address the impact of folate deficiency on hearing loss and to examine the underlying mechanisms. For this purpose, 2‐mo‐old C57BL/6J mice ( Animalia Chordata Mus musculus ) were randomly divided into 2 groups ( n = 65 each) that were fed folate‐deficient (FD) or standard diets for 8 wk. HPLC analysis demonstrated a 7‐fold decline in serum folate and a 3‐fold increase in tHcy levels. FD mice exhibited severe hearing loss measured by auditory brainstem recordings and TUNEL‐positive‐apoptotic cochlear cells. RT‐quantitative PCR and Western blotting showed reduced levels of enzymes catalyzing homocysteine (Hcy) production and recycling, together with a 30% increase in protein homocysteinylation. Redox stress was demonstrated by decreased expression of catalase, glutathione peroxidase 4, and glutathione synthetase genes, increased levels of manganese superoxide dismutase, and NADPH oxidase‐complex adaptor cytochrome b ‐245, α‐polypeptide (p22phox) proteins, and elevated concentrations of glutathione species. Altogether, our findings demonstrate, for the first time, that the relationship between hyperhomocysteinemia induced by folate deficiency and premature hearing loss involves impairment of cochlear Hcy metabolism and associated oxidative stress.—Martínez‐Vega, R., Garrido, F., Partearroyo, T., Cediel, R., Zeisel, S. H., Martínez‐Álvarez, C., Varela‐Moreiras, G., Varela‐Nieto, I., and Pajares, M. A. Folic acid deficiency induces premature hearing loss through mechanisms involving cochlear oxidative stress and impairment of homocysteine metabolism. FASEB J . 29, 418‐432 (2015). www.fasebj.org